The Trend of Targeted Therapies in Chinese Patients With Ankylosing Spondylitis: Results From a Real-Life Survey - Wen, Yiquan; Hu, Zhuoran; Xie, Baozhao; Yuan, Fei; Xie, Zhengquan; Jiang, Yutong; Lin, He; Qi, Jun; Chen, Qiyun (Frontiers in Pharmacology, 2021)
Introduction: Targeted medication, including mostly biologics and small-molecule chemical drugs, is an important therapy for ankylosing spondylitis (AS). There are still limited data on the preference of different targeted drugs in Chinese AS patients. Methods: A questionnaire-based cross-sectional study was performed on AS patients from six hospitals in three provinces in South China. Anti-rheumatic diseases’ medication history includes the recent and previous usage of biologics or Janus kinase inhibitors (JAKi) in the last complete course of treatment, disease severity, and reasons for targeted-treatment change or preference. Results: 354 of 366 participants responded to the online survey. The participants’ median age was 32 years, with a median of 7.3 years of disease duration; 79.7% were male. 63.6% of them were in the course of biologics or JAKi. Generic ETN is the most widely used and willing-to-use biologic though the proportion of its usage shrunk in the present compared with the past. The choice of original-branded ADA demonstrated an increase in usage. The preference of secukinumab and tofacitinib depicted a quick ascending trend. Conclusion: TNF-α inhibitors (TNFi) are still the most popular targeted medication for AS in China. Their price influences patients’ preferences mostly. The doctor’s recommendation is also part of the equation. Rheumatologists should pay more attention to patients’ education to formulate targeted therapeutic plans.